2021
DOI: 10.1371/journal.pone.0244163
|View full text |Cite
|
Sign up to set email alerts
|

Genomic GC content drifts downward in most bacterial genomes

Abstract: In every kingdom of life, GC->AT transitions occur more frequently than any other type of mutation due to the spontaneous deamination of cytidine. In eukaryotic genomes, this slow loss of GC base pairs is counteracted by biased gene conversion which increases genomic GC content as part of the recombination process. However, this type of biased gene conversion has not been observed in bacterial genomes, so we hypothesized that GC->AT transitions cause a reduction of genomic GC content in prokaryotic genom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…On long evolutionary timescales (at or above the level of orders), slow adaptation of genomic GC content may optimize whole taxonomic clades to the nutrient availabilities in that clade's typical ecological niche. Thus, metabolic strategies that are well-adapted to the nutrient requirements of the proteome may be one of many potential factors shaping GC content evolution, including biases in mutations and their repair (27)(28)(29), DNA stability (30), and GC-biased gene conversion (gBGC) (31).…”
Section: Discussionmentioning
confidence: 99%
“…On long evolutionary timescales (at or above the level of orders), slow adaptation of genomic GC content may optimize whole taxonomic clades to the nutrient availabilities in that clade's typical ecological niche. Thus, metabolic strategies that are well-adapted to the nutrient requirements of the proteome may be one of many potential factors shaping GC content evolution, including biases in mutations and their repair (27)(28)(29), DNA stability (30), and GC-biased gene conversion (gBGC) (31).…”
Section: Discussionmentioning
confidence: 99%
“…While there are many examples of microbial genomes becoming more AT rich 32 there are so few examples of genomes becoming more GC rich that it was recently suggested that it may not happen at all 16 . Some examples have however been observed in the microbial world although the increase is minuscule 14 , 15 , 41 .…”
Section: Resultsmentioning
confidence: 99%
“…Environmental influence on genomic GC content in prokaryotes appears to be mediated, at least to some extent, as selective pressures 14 , 15 . In this respect, it is of interest to note that large drops in genomic GC content is wide-spread in prokaryotes 7 while examples of substantial increase is practically non-existent as of now 16 , although smaller increases are documented 13 , 15 , 17 , 18 . Examination of AT- and GC mutation rates in prokaryotes points to an AT bias also in recombining microbes while AT GC substitutions are more likely to be retained 9 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Prokaryotes in high-temperature environments have higher GC content than those in low temperatures, suggesting that higher GC contents may be related to thermal adaptation ( 16 ). Mutation events in the DNA, ecological niche conditions, and above all, horizontal gene transfer affect the GC content in bacterial genomes ( 17 ). For the bacteria in this study, the distant signatures between species and the percentages of GC content in their genomes also seem to be a genetic characteristic of these species.…”
Section: Discussionmentioning
confidence: 99%